Assessment of GIC Based On Transfer Function Analysis. Issue 12 (11th December 2017) - Ingham, M.; Rodger, C. J.; Divett, T.; Dalzell, M.; Petersen, T.
Abstract: Transfer functions are calculated for periods between 2 and 1, 000 min between geomagnetically induced currents (GIC) measured at three transformers in the South Island of New Zealand and variations in the horizontal components of the geomagnetic field measured at the Eyrewell Observatory near Christchurch. Using an inverse Fourier transform, the transfer functions allow the GIC expected in these transformers to be estimated for any variation of the inducing magnetic field. Comparison of the predicted GIC with measured GIC for individual geomagnetic storms shows remarkable agreement, although the lack of high‐frequency measurements of GIC and the need for interpolation of the measurements lead to a degree of underestimation of the peak GIC magnitude. An approximate correction for this is suggested. Calculation of the GIC for a magnetic storm in November 2001 that led to the failure of a transformer in Dunedin suggests that peak GIC were as large as about 80 A. Use of spectral scaling to estimate the likely GIC associated with a geomagnetic storm of the magnitude of the 1859 Carrington Event indicates that GIC of at least 10 times this magnitude may occur at some locations. Although the impact of changes to the transmission network on calculated transfer functions remains to be explored, it is suggested that the use of this technique may provide a useful check on estimates of GIC produced by other methods such as thin sheet modeling. Plain Language Summary: Rapid changes in Earth's magnetic field, such as occur during a magnetic storm, induce electric currents in the ground. These currents, known as geomagnetically induced currents (GIC), are able to enter a power transmission network through the ground connection of a substation transformer. Not only can such currents cause damage to transformers, but in extreme situations they may cause failure of the entire power transmission network. We relate measurements of GIC in the New Zealand power transmission network to variations in the magnetic field at a local magnetic observatory. This allows us to construct mathematical relationships between GIC and magnetic field variations which enable us to predict the magnitude of GIC that might occur in the event of a magnetic storm such as the so‐called Carrington Event of 1859—the largest such storm ever recorded. It is found that GIC of almost 1, 000 A might occur. Key Points: Transfer functions relating GIC measured at New Zealand substations to magnetic field variations at Eyrewell observatory are calculated Calculated transfer functions are able to accurately reproduce observed GIC during magnetic storms The GIC to be expected during a storm of the magnitude of the Carrington Event are estimated